2022
DOI: 10.1093/brain/awac088
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymph nodes and ovarian teratomas as germinal centres in NMDA receptor-antibody encephalitis

Abstract: Autoantibodies against the extracellular domain of the N-methyl-d-aspartate receptor (NMDAR) NR1 subunit cause a severe and common form of encephalitis. To better understand their generation, we aimed to characterize and identify human germinal centres actively participating in NMDAR-specific autoimmunization by sampling patient blood, CSF, ovarian teratoma tissue and, directly from the putative site of human CNS lymphatic drainage, cervical lymph nodes. From serum, both NR1-IgA and NR1-IgM were detected more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 53 publications
3
58
0
Order By: Relevance
“…Written informed consent was obtained from all participants, including 14 disease controls (with autoimmune encephalitis, n = 11, or migraine, n = 3; select controls also in ref. 47 ). For patients and controls, demographics, past and current immunotherapies, and sampling times are detailed in SI Appendix , Tables 1 and 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consent was obtained from all participants, including 14 disease controls (with autoimmune encephalitis, n = 11, or migraine, n = 3; select controls also in ref. 47 ). For patients and controls, demographics, past and current immunotherapies, and sampling times are detailed in SI Appendix , Tables 1 and 2 .…”
Section: Methodsmentioning
confidence: 99%
“… 26 In NMDAR encephalitis, tertiary lymphoid architectures in ovarian teratomas were suggested, and a production of NMDAR autoantibodies was detected from cultured teratoma explants and dissociated intratumoral B cells and from 3/7 cultures of cervical lymph nodes. 27 Our data point to a relevance of germinal center reactions also in GAD65-Ab SD.…”
Section: Discussionmentioning
confidence: 52%
“…Additionally, because T cells are predominantly found in the cerebrospinal fluid (CSF) of affected people while B cells are scarce ( 17 ), some prior studies have suggested that NMDAR-E onset could be potentially triggered by the activation of T cells in the periphery and CNS ( 13 ). Indeed, current pathological examination and postmortem reports further support the observation that the different effector T helper (Th) cells, such as Th1 and Th17 cells, could extensively be infiltrated in the tissues ( 11 , 13 , 14 , 18 ). In particular, previous studies have demonstrated that Th cells can significantly enhance antibody-secreting cell (ASC)-mediated antibody responses, as mice were actively immunized with conformationally stabilized NMDAR protein and both ASCs and CD4+ T cells demonstrated extensive infiltration into the hippocampus ( 19 ).…”
Section: Introductionmentioning
confidence: 62%
“…Furthermore, prior studies in mouse models have revealed that autoimmune antibodies can activate both astrocytes and microglia, and then these cells can release cytokines such as IL-1β and IL-12 to promote the epileptic occurrence and enhance the immune effects of Th1 cells ( 77 , 78 ). In addition, activated follicular helper T cells and follicular dendritic cells can release CXCL13 to promote the immune response ( 18 ). These immune cells can facilitate inflammation, especially in the early stages of autoimmune encephalitis ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%